The behaviour of masonry wall constituted by hollow blocks: \b strength correlation - Muhamad Amru Mustafa (School of Environmental Engineering, University Malaysia Perlis, 2012)
This paper focuses on the development of the compressive strength correlation between the individual block, prism and basic wall panel for load bearing interlocking hollow mortarless blocks. The interlocking blocks used were developed by the Proven Holding Berhad for industrialized building system (IBS). The blocks consisted of stretcher, corner and half blocks. Six individual block units from each type were tested under compression. The size of prism is 0.4 m x 0.6 m. The compressive strengths of prism assembled by stacking two stretcher blocks and two half blocks were evaluated. In addition, basic wall panelhaving a dimension of 1.2 m 0.4 m were assembled and tested under axial compressive loads. The results obtained were compared with those found in bonded masonry BS 5628 Part 1:1992 were used for predicting of the compressive capacity of the bonded masonry. The interlocking mechanism, crack patterns and failure mechanism of the interlocking masonry specimens are highlighted and discussed. The correlations between the compressive strength of the interlocking masonry individual block (fcb), prism (fcp) and standard panel (fcw) found in this analysis were fcp = 0.608fcb, fcw = 0.870fcp and fcw = 0.804fcb. Test results indicate that the interlocking mechanism and strength of the block in the load - bearing wall was satisfactory.